Estimation of Torg's Ratio in adult female population of Rajasthan - Savita Choudhary; Prabhakaran Kattimuthu; Lalit kumar Jain (Asian Journal of Medical Research, 2013)
To estimate the midsagittal diameter of the cervical spinal canal in normal healthy adult female population of Rajasthan, to set the normal range of the Torg's ratio (canal/body ratio) for the cervical spinal canal in adult female population of Rajasthan, to Correlate sex and age with mid sagittal diameter of cervical spinal canal and to Correlate sex and age with Torg's ratio (canal/ body) ratio.50 healthy adult females, whose age ranging from 20-40 years formed the subject for the current study. Plain X-rays of cervical spine (Lateral view) were studied with the help of view box and the diameters measured through C3 to C7 vertebrae using vernier callipers .Finally Torg's ratio was calculated .The mean values of Torg's ratio at C3 were 0.98, C4 was 1.00, C5 was 0.98, C6 was0.97 and C7 was 0.97. : The above mentioned values are normal values of Torg's ratio related to the cervical vertebrae of adult female population of Rajasthan. In case of any deviation from the average values, we can detect the narrowing or widening of the cervical spinal canal. It may prove as useful information to evaluate and asses the problems of cervical pain and stenosis of Rajasthan female population